LPP Proposal on the change of the current syllabus of English of the students whose major is Math - Abdurazokov, Ulugbek (Журнал иностранных языков и лингвистики, 2021)
The current paper tries to investigate all the possible nuances of existing syllabuses of English taught to students whose major is Math and aims to provide with alternate solutions and recommendations. The findings obtained will serve as an asset to provide practical implications for the policy makers, language experts, and teachers in the Higher Education in Uzbekistan.